Census of Publicly Funded Forensic Crime Laboratories, 2020 ([Verlag nicht ermittelbar], 2024)
This data collection contains data from the 2020 Census of Publicly Funded Forensic Crime Laboratories (CPFFCL). The CPFFCL collected data on organizational characteristics, functions, budget, staffing, workload, resources, and quality assurance practices of publicly funded forensic crime laboratories operating in the U.S. and serving federal, state, and local jurisdictions. The CPFFCL includes crime labs that employed one or more full-time scientists who possess a minimum of a bachelor's degree in chemistry, physics, biology, criminalistics, forensic science or a closely related field and whose principal functions are examining physical evidence in criminal matters and providing reports and testimony to courts of law with respect to such evidence. Private laboratories were excluded from the CPFFCL. Laboratories may operate independently or as part of a larger system. Respondents to the CPFFCL could choose to respond as individual labs or as one system. A total of 423 individual labs, constituting 326 standalone labs and multilab systems, received the questionnaire. A total of 382 (90%) individual labs responded to the 2020 CPFFCL and 293 (90%) standalone labs and multilab systems responded. For the 2020 study, data were collected from July 2021 to February 2022. The Bureau of Justice Statistics (BJS) first surveyed forensic crime laboratories in 1998, focusing solely on agencies that performed DNA analysis. The National Institute of Justice (NIJ) funded the 1998 study as part of its DNA Laboratory Improvement Program. The BJS' National Study of DNA Laboratories was repeated in 2001. An expanded version of the data collection, called the Census of Publicly Funded Forensic Crime Laboratories, was first conducted among all forensic crime laboratories in 2002.